Digital learning media in elementary science: stimulating or demotivating? - Lubis, Maesaroh (Assyfa Journal of Multidisciplinary Education, 2023)
This research focuses on efforts to understand the influence of digital learning media on students' learning motivation in science subjects at the elementary school (SD) level. This research is a systematic literature review that evaluates the effectiveness of using digital learning media in science teaching from 2020 to 2024. The theories bridged include visual learning theory and learning motivation theory, which are integrated into teaching practice through instructional videos, animations, and multimedia presentations. This research reviewed 11 studies involving elementary school students from various regions and countries, with a total participation of 1401 students. The research results show that using digital learning media in science teaching can significantly increase student motivation and engagement. However, this media application still faces various challenges, such as the need for teachers to understand technology, limited access to digital tools, and inadequate training. For instance, some teachers reported difficulty navigating the software, while others needed help incorporating the media into their lesson plans. These challenges can lead to inconsistent implementation and limited effectiveness of digital learning media. To address this, the research recommends increasing specific training for teachers on using digital learning media, providing more comprehensive access to these technologies, and supporting policies that encourage technology integration in science curricula. Thus, this research emphasizes the importance of integrating digital learning media in science teaching to improve the quality of learning and student learning outcomes. This research also proposes concrete steps for implementation, such as ongoing training programs for teachers and regular evaluation of the effectiveness of using digital learning media in the classroom.